A volumetric three-dimensional digital light photoactivatable dye display - Shreya K. Patel (Nature Portfolio, 2017)
Despite living in a three-dimensional world, almost all information in our society is conveyed in a two-dimensional format. Here, the authors provide a technique for the generation of spatially accurate and high-resolution three-dimensional images using fluorescent photoswitch chemistry.